Two random amplified polymorphic DNA (RAPD) markers linked to CMV-B2 resistance gene (Creb-2) in melon cultivar Yamatouri were cloned and sequenced to design sequence characterized amplified region (SCAR) markers for detection of CMV-B2 resistance gene (Creb-2) in melon. SCOPE14 derived from OPE-14 yielded a single DNA band at 541 bp, while SCAPB05 derived from APB-05, yielded a single DNA band at 1,046 bp, respectively. Segregation of SCOPE14 and SCAPB05 markers in bulk of F2 plants demonstrate - BUDI SETIADI DARYONO; KENJI WAKUI; KEIKO T. NATSUAKI (Bogor Agricultural University, Indonesia, 2009)
Two random amplified polymorphic DNA (RAPD) markers linked to CMV-B2 resistance gene (Creb-2) in melon cultivar Yamatouri were cloned and sequenced to design sequence characterized amplified region (SCAR) markers for detection of CMV-B2 resistance gene (Creb-2) in melon. SCOPE14 derived from OPE-14 yielded a single DNA band at 541 bp, while SCAPB05 derived from APB-05, yielded a single DNA band at 1,046 bp, respectively. Segregation of SCOPE14 and SCAPB05 markers in bulk of F2 plants demonstrated that they were co-segregated with RAPD markers from which the SCAR markers were originated. Furthermore, results of SCAR analysis in diverse melons showed SCAPB05 primers obtained a single 1,046 bp linked to Creb-2 in resistant cultivars Sanuki-shirouri and Kohimeuri. However, SCOPE14 failed to detect Creb-2 in diverse melons. Results of this study revealed that SCAR analysis not only confirmed melons that had been clearly scored for resistance to CMV-B2 by RAPD markers, but also clarified the ambiguous resistance results obtained by the RAPD markers. Key words: Cucumis melo L., Creb-2, RAPD, SCAR